Strategi Fundraising Zakat Pada Baznas Provinsi Sumatera Barat - Nanda Nanda (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Badan Amil Zakat Nasional is a nonstructural government agency that is independentand responsible to the president through ministers. BAZNAS is an institution that is authorized to carry out the task of managing zakat nationally. The purpose of this study is to determine the strategy carried out by BAZNAS of West Sumatra Province in zakat fundraising activities. The main problem in this study is the strategy carried out by the National Amil Zakat Agency of West Sumatra Province in zakat fundraising activities. The type of research that the author uses is field research with qualitative methods (field research). The data collection techniques that the author did were field observations, interviews with the National Amil Zakat Agency and documentation. Data analysis techniques are data reduction, data presentation and drawing conclusions. The results of this study show that the fundraising strategy carried out by the National Zakat Agency of West Sumatra Province is to use two fundraising methods, namely online and offline methods (direct and indirect). Direct fundraising is to approach local governments, conduct hearings with institutions, socialize zakat, carry out zakat pick-up services and indirect fundraising such as maximizing the use of electronic media and print media. The main obstacle is that the fundraising strategy prepared by BAZNAS of West Sumatra Province has been fully implemented in the field but the level of effectiveness is still low. BAZNAS of West Sumatra Province has not optimally worked on the potential of zakat in West Sumatra. There are still many muzzaki that cannot be folow up from BAZNAS, and the lack of human resources at BAZNAS West Sumatra Province.